2006
DOI: 10.1111/j.1469-8137.2006.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Species composition of an ectomycorrhizal fungal community along a local nutrient gradient in a boreal forest

Abstract: Summary• Soil abiotic factors are considered to be important in determining the distribution of ectomycorrhizal (ECM) fungal species; however, there are few field data to support this. Here, we relate ECM species distributions to changes in soil chemistry along a short (90-m), natural nutrient gradient.• The ECM community was characterized, using morphological and molecular techniques, in soil samples collected at 10-m intervals.• There were pronounced changes in ECM fungal community structure along the transe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
139
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 34 publications
18
139
1
Order By: Relevance
“…e.g. Toljander et al 2006;Rineau and Garbaye 2009;Walthert et al 2006). The F horizon was small (0-2 cm) at the beginning of the experiment and increased to about 3 cm in the year 2007 (data not shown).…”
Section: Changes Of Fungal Communities Over Time Irrespective Of N Trmentioning
confidence: 99%
See 1 more Smart Citation
“…e.g. Toljander et al 2006;Rineau and Garbaye 2009;Walthert et al 2006). The F horizon was small (0-2 cm) at the beginning of the experiment and increased to about 3 cm in the year 2007 (data not shown).…”
Section: Changes Of Fungal Communities Over Time Irrespective Of N Trmentioning
confidence: 99%
“…Changes of soil properties due to fertilization and their possible effects on the fungal communities Soil abiotic factors are considered to be important in determining the distribution of ectomycorrhizal fungal species (Erland and Taylor 2002;Toljander et al 2006). Soil base saturation, pH and organic matter content are among the most important factors governing the distribution of macrofungi (Agerer et al 1998;Erland and Taylor 2002;Wallenda and Kottke 1998;Kernaghan 2005).…”
Section: Response Of Saprobic Species To Fertilizationmentioning
confidence: 99%
“…Methods of scoring ectomycorrhizas by number of root tips versus DW provide a different picture of species composition; however, we found a relationship between the two measures and we can conclude that the number of EcM root tips is more suitable and less time consuming if we combine with a meticulous morpho-anatotyping study. The use of transects across gradients are helpful to describe maximum variation over short distances in a short period of time (Kent and Coker 1999; Toljander et al 2006). However, in the current study the spatial arrangement of samples indicated that over short distances the dissimilarity was lower in contrast with the longer distances, suggesting that a random sampling across a wider plot could be more suitable in Scots pine woodlands.…”
Section: Discussionmentioning
confidence: 99%
“…Soil conditions have been suggested to be important factors affecting mycorrhizal fungi (Erland and Taylor 2002;Toljander et al 2006;Scatollin et al 2008;Alzetta et al 2012;Newbound et al 2012). …”
Section: Discussionmentioning
confidence: 99%